Strategi CRM dalam Meningkatkan Loyalitas Pelanggan Melalui Program Garudamiles - Dewi, Anggia Sasmita; Wahyudin, Aep (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2021)
The purpose of this study is to find out how Garuda Indonesia acquires new customers (Acquire), increases sales (Enhance) and maintains relationships with customers in the long and short term (Retain) through the GarudaMiles program. This study uses the concept of Customer Relationship Management (CRM) according to Kalakota and Robinson (2001), and uses the constructivism paradigm with an interpretive approach and the use of descriptive analysis methods. This study uses data collection techniques through observation, in-depth interviews and documentation. The results of this study found that PT. Garuda Indonesia has implemented a Customer Relationship Management Strategy to increase customer loyalty with the GarudaMiles program, namely 1). Stages of acquiring new customers, with four things, namely, identifying customer needs, media information and promotions, competitor analysis, and after-purchase evaluation, 2). There are three stages of profitability, namely, profiling and customer communication, understanding customer needs, and developing potential customers from the database, 3). There are four stages of customer retention, namely building customer emotions and service quality, giving satisfaction, customer loyalty, and retaining customers.